Ku tak sanggup - Kris Dayanti; Warner Music (Kuala Lumpur : Warner Music (Malaysia), 1999)
Terdapat dua buah lagu berirama pop yang dipetik dari album Menghitung Hari.
Ku Tak Sanggup (3:25)-- Jangan Biarkan (4:32).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, Indonesian; Popular music